Towards the Security Analysis of the Five Most Prominent IPv4aaS Technologies - Al-Azzawi, Ameen (Acta Technica Jaurinensis, 2020)
This paper surveys the five most important technologies for IPv4aaS (IPv4-as-a-Service), namely 464XLAT, DS-Lite (Dual-Stack Lite), lw4o6 (Lightweight 4over6), MAP-E and MAP-T. The aim of our effort is to identify the potential security issues within these technologies. We plan to perform their security analysis following the STRIDE approach, which stands for spoofing, tampering, repudiation, information disclosure, denial of service and elevation of privilege. We give a short introduction for the method. Within the five IPv4aaS technologies, we focus on 464XLAT, its architecture and operation. We construct a DFD diagram suitable for its security analysis according to the STRIDE methodology, thus making the first steps towards finding its potential vulnerabilities and seeking for their mitigations.